Causes of Decreasing Hospital Visit during the Covid-19 Pandemic - Megawati, Devvy; Ratri, Devita Rahmani; Erzi, Alfan (Jurnal Kedokteran Brawijaya, 2021)
The problem of decreasing bed utilization resulted in a decrease in hospital income during the Covid-19 pandemic, including in a class D private hospital, Tulungagung, that experienced a 32.5% decrease in revenue. The decrease in hospital income has made the hospital suffer losses and, at the same time, threatened the cash flow, the operating expenses, and the continuity of service operations. The study was conducted to identify the root cause of the decreasing patient visits at the hospital. The research was conducted with a case study approach at a private hospital in Tulungagung in September and October 2020. The data were collected using a Focus Group Discussion (FGD) with eight respondents who were determined based on purposive sampling. Data were analyzed using Fishbone diagrams and priorities were set based on cumulative percentages. The public's stigma about hospitals during the Covid-19 pandemic and the cost of rapid tests are the two root causes that are suspected of contributing to the decline in patient visits at the hospital.